Sertraline behavioral response associates closer and dose-dependently with cortical rather than hippocampal serotonergic activity in the rat forced swim stress - Mikail, H. G.; Dalla, C; Kokras, N; Kafetzopoulos, V; Papadopoulou-Daifoti, Z. (Physiol Behav, 2012)
The rat Forced Swim Test (FST) is widely used to investigate the response to antidepressant treatment. Selective serotonin reuptake inhibitors (SSRIs) elongate swimming duration during the FST, while climbing duration is unaffected. In the present study, we aimed to correlate behavioral effects of the SSRI sertraline in the FST with respective changes in the serotonergic activity of the hippocampus and the prefrontal cortex. Male rats were subjected to the standard FST (two swim sessions in two consecutive days) and between the two sessions they received three i.p. injections of sertraline (10 mg/kg or 40 mg/kg) or vehicle. All rats were killed immediately after the second FST session. Unstressed animals received the same administration schemes and were killed in equivalent time-points. Serotonin and its metabolite 5-HIAA were assayed in the hippocampus and the prefrontal cortex with the use of high-performance liquid chromatography (HPLC-ED) and their ratio 5-HIAA/5-HT was calculated. Sertraline enhanced swimming and decreased immobility duration at both doses. Serotonergic activity was not altered by the 2-day swim stress in either brain region, while subchronic sertraline treatment enhanced 5-HT levels and decreased 5-HIAA/5-HT in the hippocampus and the prefrontal cortex. The serotonin turnover rate (5-HIAA/5-HT ratio) decrease is probably indicative of reduced 5-HT metabolism, as a result of 5-HT reuptake inhibition. This effect was significant in the prefrontal cortex of unstressed rats only after a higher dose of sertraline. In the prefrontal cortex, but not in the hippocampus, immobility duration was negatively correlated with 5-HT tissue levels, whereas swimming duration was positively correlated with 5-HT. These results indicate that after antidepressant treatment, behavior during the FST can be predictive of respective serotonergic changes, especially in the prefrontal cortex.
Keywords: Animals; Disease Models, Animal; Dose-Response Relationship, Drug; Hippocampus/drug effects/*physiology; Hydroxyindoleacetic Acid/metabolism; Immobility Response, Tonic/drug effects/physiology; Male; Prefrontal Cortex/drug effects/*physiology; Rats; Rats, Wistar; Serotonergic Neurons/drug effects/metabolism/*physiology; Serotonin/metabolism; Sertraline/*pharmacology/therapeutic use; Stress, Psychological/drug therapy/*physiopathology; Swimming/physiology